2006
DOI: 10.1080/17470910600989797
|View full text |Cite
|
Sign up to set email alerts
|

The development and neural basis of referential gaze perception

Abstract: Infants are sensitive to the referential information conveyed by others' eye gaze, which could be one of the developmental foundations of theory of mind. To investigate the neural correlates of gaze-object relations, we recorded ERPs from adults and 9-month-old infants while they watched scenes containing gaze shifts either towards or away from the location of a preceding object. In adults, object-incongruent gaze shifts elicited enhanced ERP amplitudes over the occipito-temporal area (N330). In infants, a sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
76
3

Year Published

2008
2008
2013
2013

Publication Types

Select...
3
3
3

Relationship

2
7

Authors

Journals

citations
Cited by 91 publications
(94 citation statements)
references
References 60 publications
(68 reference statements)
15
76
3
Order By: Relevance
“…Hence, response characteristics in this task were associated with later emerging social and non-social characteristics of autism, suggesting some interdependence of social and non-social circuits early in development. This pattern is broadly consistent with the suggestion that while the P1 and N290 are sensitive to the visual analysis of face and gaze information, the P400 is associated with top-down processing of gaze information (Elsabbagh, Volein, Csibra, et al, 2009;Senju, Johnson, & Csibra, 2006). In other words, it is both the overall response to faces together with functional interpretation of gaze information in infancy which map onto the variability in autism-related characteristics in toddlerhood.…”
Section: Infants At-risk For Autism: Implications For Typical and Atysupporting
confidence: 86%
“…Hence, response characteristics in this task were associated with later emerging social and non-social characteristics of autism, suggesting some interdependence of social and non-social circuits early in development. This pattern is broadly consistent with the suggestion that while the P1 and N290 are sensitive to the visual analysis of face and gaze information, the P400 is associated with top-down processing of gaze information (Elsabbagh, Volein, Csibra, et al, 2009;Senju, Johnson, & Csibra, 2006). In other words, it is both the overall response to faces together with functional interpretation of gaze information in infancy which map onto the variability in autism-related characteristics in toddlerhood.…”
Section: Infants At-risk For Autism: Implications For Typical and Atysupporting
confidence: 86%
“…While this finding indicates that infants expect a referent object for a gaze shift, neuroimaging studies demonstrated that adults would also hold the opposite expectation: that gaze shifts would be directed towards the sole object on the scene (Pelphrey et al, 2003(Pelphrey et al, , 2005. Although event-related potential studies suggest that this might also be true for infants (Senju, Johnson, & Csibra, 2006), there has been no behavioural evidence on this issue so far.…”
Section: Introductionmentioning
confidence: 93%
“…In addition to causal opacity, another factor that is thought to be important in the emergence of "efficiency blindness" and in the aforementioned selective responsiveness in imitation is whether the human demonstrator presents his/her action in an ostensive-communicative-referential manner. Recent studies on infant social cognition provide convergent evidence indicating that young preverbal infants are prone to show special sensitivity and preference for a basic set of ostensive-communicative signals (such as direct eye contact, being addressed in motherese, turn-taking contingent reactivity- Ricciardelli et al 2000;Cleveland and Striano 2007;Nielsen 2006;Senju and Csibra 2008;Yoon et al 2008) and referential cues (such as gaze-shift or pointing- Teuscher and Triesch 2007;Senju et al 2006;Grossmann et al 2008;. It has been argued that human infants are biologically prepared to interpret such cues as expressing the other's overt communicative intention towards them to convey new and relevant information about referents (see Gergely and Csibra 2006;Gergely et al 2007;Csibra and Gergely 2009).…”
Section: Introductionmentioning
confidence: 99%